Aujeszky's Disease/Pseudorabies in Cats: ABCD guidelines on prevention and management. Issue 7 (July 2013) - Thiry, Etienne; Addie, Diane; Belák, Sándor; Boucraut-Baralon, Corine; Egberink, Herman; Frymus, Tadeusz; Gruffydd-Jones, Tim; Hartmann, Katrin; Hosie, Margaret J; Lloret, Albert; Lutz, Hans; Marsilio, Fulvio; et al.
Overview: Although pseudorabies in swine – Aujeszky's disease – has been eradicated from many pork-producing countries, the virus may still lurk in other vertebrate species and cause feline cases. Infection occurs through the ingestion of uncooked meat and organ material and presents as an acute encephalitis with a short incubation period and a rapidly fatal outcome. The ABCD considers this reason enough to include a review of this, now very rare, condition in this Special Issue.